Gut Ischemia Reperfusion Injury Induces Lung Inflammation via Mesenteric Lymph-Mediated Neutrophil Activation - Ma, Yonggang; Zabell, Taylor; Creasy, Alexandra; Yang, Xiaoyuan; Chatterjee, Victor; Villalba, Nuria; Kistler, Erik B.; Wu, Mack H.; Yuan, Sarah Y. (Frontiers in Immunology, 2020)
Gut ischemia/reperfusion (I/R) injury is a common clinical problem associated with significant mortality and morbidities that result from systemic inflammation and remote organ dysfunction, typically acute lung injury. The mechanisms underlying the dissemination of gut-derived harmful mediators into the circulation are poorly understood. The objective of our study was to determine the role of mesenteric lymphatic circulation in the systemic and pulmonary inflammatory response to gut I/R. Using a murine intestinal I/R model, we evaluated whether and how blocking mesenteric lymph flow affects the inflammatory response in local tissues (gut) and remote organs (lungs). We further explored the mechanisms of post-I/R lymph-induced systemic inflammation by examining neutrophil activity and interaction with endothelial cells in vitro. Mice subjected to intestinal I/R displayed a significant inflammatory response in local tissues, evidenced by neutrophil infiltration into mucosal areas, as well as lung inflammation, evidenced by increased myeloperoxidase levels, neutrophil infiltration, and elevated microvascular permeability in the lungs. Mesenteric lymph duct ligation (MLDL) had no effect on gut injury per se, but effectively attenuated lung injury following gut I/R. Cell experiments showed that lymph fluid from post-I/R animals, but not pre-I/R, increased neutrophil surface CD11b expression and their ability to migrate across vascular endothelial monolayers. Moreover, post-I/R lymph upregulated neutrophil expression of pro-inflammatory cytokines and chemokines, which was mediated by a mechanism involving nuclear factor (NF)-κB signaling. Consistently, gut I/R activated NF-κB in lung neutrophils, which was alleviated by MLDL. In conclusion, all these data indicate that mesenteric lymph circulation contributes to neutrophil activation and lung inflammation following gut I/R injury partly through activating NF-κB.